Allelopathic Effects of Annual Weeds on Germination and Seedling Growth of Oilseed Radish (Raphanus sativus L. var. oleiformis Pers.) - Tsytsiura, Yaroslav (2024)
The allelopathic effects of 54 weed species were studied on oilseed radish (Raphanus sativus L. var. oleiformis Pers.) in Petri dishand soil bioassays. Weed extracts were prepared at concentrations of 0.25,0.5,1.0, 2.0, 4.0, 8.0 and 16.0% and assayed on seedgermination and seedling growth. They showed a species-specific effect when tested in the range of concentrations of 1.0–4.0%.Seed germination was less inhibited in soil than in Petri dish assays. Indexes of allelopathic potential (AP) were separately calculatedfor germination (APG) and seedling growth (APRG for roots and APSG for shoots). They were in the range of 0.27–0.72 and 0.16–0.70,respectively. The weeds were classified according to their APSG and APRG indexes, and the percentage of appearance frequency(F) in oilseed radish fields, from more to less harmful, as: Amaranthus retroflexus > Echinochloa crus-galli (L.) P. Beauv > Setaria glaucaL. > Chenopodium album L. > Brassica napus L. > Galinsoga parviflora Cavanilles > Sinapis alba L. > Tripleurospermum maritimum(L.) Koch > Raphanus sativus L. var. oleiformis Pers. > Polygonum lapathifolium (L.) Delarbre > Setaria viridis (L.) Palisot de Beauvois >Barbarea vulgaris Brown > Brassica campestris (L.) Janchen > Lactuca serriola L. > Thlaspi arvense L. > Senecio vernalis (Waldstein &Kitaibel) Alexander > Lepidium draba L.